Parasitic Contamination of Street Food Samples From School-Based Food Vendors of Dhaka City, Bangladesh (Bangladesh Journal of Zoology, 2023)
Street food is an old notion that arose from the need of quick access of light food to satisfy hunger. With the mention of street food in Bangladesh, a picture is visualized which includes open stalls with uncovered food, unawareness of vendors about hygienic practices, lack of safe source of water for cleaning and preparing food, increasing pollution in surrounding environment leading to infestation with various parasites and causing diarrhoeal diseases in people. The aim of the present study was to determine the prevalence of parasites in school-based street foods in Dhaka city. A total of 200 food samples were examined containing three representative types of street foods: tamarind water of snacks (79 samples), sliced fruits (71 samples) and fruit juices (50 samples) using Formal-ether concentration technique. Among them, 164 (82%) samples were contaminated with Entamoeba histolytica, Blastocystis hominis, Cystoisospora belli, Diphyllobothrium latum, Hymenolepis diminuta, Hymenolepis nana, Ascaris lumbricoides, Enterobius vermicularis, Trichuris trichiura and Ancylostoma duodenale. C. belli was the most prevalent (38%), followed by A. lumbricoides (33%) and B. hominis (33%). While comparing the parasite prevalence in three types of street foods, the highest prevalence was observed for C. belli (21.5% in tamarind water of snacks, 6.5% in sliced fruits and 10% in fruit juices) followed by A. lumbricoides, B. hominis and D. latum. There were significant associations (p